Analysis of the quality of cytopathology samples and their impact on diagnosis (Research, Society and Development, 2025)
Cytopathology is an essential branch of study in the diagnosis of diseases, especially in the screening of pathologies such as cancer. The general objective of this study is to analyze the quality of cytopathology samples and their impact on diagnosis, emphasizing the importance of rigorous practices in all stages of the process, from sample collection to analysis. The methodology used consists of an integrative literature review, which covers scientific articles published between 2014 and 2024. The research was carried out in databases such as Scientific Electronic Library Online (SCIELO), Lilacs and PubMed, using descriptors related to cytopathology and sample quality. Inclusion and exclusion criteria were rigorously applied to ensure the relevance and quality of the selected studies. The expected results indicate that the implementation of quality standards and rigorous control in the stages of sample collection, fixation and transportation is crucial to ensure accurate diagnoses. The research also aims to contribute to the training of professionals in the field, academics and researchers, highlighting the relevance of sample quality in cytopathology and its direct impact on the accuracy of diagnoses for patients.